Economic impact of antifungal treatment in IFD by Candida species: anidulafungin administration as a cost-effective alternative for critical care patients. Issue 1 (5th June 2014) - Cattel, F; Ancona, F; Chiumente, M; Miliacca, A; Motta, I; De Rosa, F G
Abstract : Objectives: To evaluate the potential savings resulting from the substitution of caspofungin and liposomal amphotericin B with anidulafungin in intensive care units (ICUs), where appropriate, for the treatment of invasive fungal disease. Methods: We conducted a retrospective analysis on patients admitted to two ICUs at S. Giovanni Battista hospital in Turin (IT). Included patients were admitted during the year 2010 for ≥3 days. We evaluated the substitutability index of caspofungin and liposomal amphotericin B with anidulafungin. According to the index, we created an economical model in order to project the potential savings for the entire hospital. Results: A total of 179 medical records were included in the analysis. We evaluated 488 doses of antifungals administered, including: 174 anidulafungin, 209 caspofungin and 105 liposomal amphotericin B. Anidulafungin was found to be a possible substitute for a total of 166 doses of caspofungin and 43 doses of liposomal amphotericin B. The substitutability index was 79.4% and 40.9%, respectively, for caspofungin and liposomal amphotericin B. The projected savings would be €37 300 for all of the departments examined. If this antifungal drug had not been included in the hospital formulary, and thus not administered in the two ICUs, the hospital would have spent €42 747 more. According to our model the differential cost is equal to 37 300+42 747=€80 047. Conclusions: The savings we obtained is proportional to our substitutability index based on a sample of patients admitted to our ICUs. We assume that highly specialised hospitals may obtain an index higher than the one we obtained. Therefore, greater savings proportional to the number of patients treated are expected.